Morphology of setae on the coxae and trochanters of theraphosine spiders (Mygalomorphae: Theraphosidae) - Lima, Arthur Galleti [UNESP]; Guadanucci, José Paulo Leite [UNESP] (American Arachnological Society, 2018)
Mygalomorphae spiders have several cuticular structures, such as stridulating, sensory and urticating setae, which offer great potential for phylogenetic studies. Spiders of the subfamily Theraphosinae have stridulating setae that aid in group taxonomy, having been found in numerous genera including: Acanthoscurria Ausserer, 1871, Aguapanela Perafán, Cifuentes & Estrada-Gomez, 2015, Citharacanthus Pocock, 1901, Cyrtopholis Simon, 1892, Grammostola Simon, 1892, Hemirrhagus Simon, 1903, Lasiodora C. L. Koch, 1850, Longilyra Gabriel, 2014, Pamphobeteus Pocock, 1901, Phormictopus Pocock, 1901 and Theraphosa Thorell, 1870. Some distinct bristle-like setae were examined using scanning electron microscopy with the following objectives: (1) to sample and describe the diversity of setae on the coxae and trochanters of representatives of the subfamily Theraphosinae; and (2) to code morphological characters useful for phylogenetics. We used a previously published phylogenetic matrix, with modifications to those characters that scored stridulatory setae, and analyzed these data using parsimony with implied weighting. Setae of the same type were found in Acanthoscurria, Brachypelma Simon, 1891, Cyrtopholis, Phormictopus and Theraphosa (claviform stridulating setae). A second type, which we name velvet stridulating setae, emerged as an autapomorphy of the genus Lasiodora, and spiniform stridulating setae were recovered as an autapomorphy of the genus Pamphobeteus. Some other setae similar to those of Lasiodora, named plumose stridulating setae, were found in Nhandu Lucas, 1983, Proshapalopus Mello-Leitaõ, 1923, Pterinopelma Pocock, 1901 and Vitalius Lucas, Silva & Bertani, 1993.
Keywords: cladistics; phylogeny; stridulating setae; Theraphosinae